2017
DOI: 10.1177/0310057x1704500615
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and the Learning Environment of Anaesthetic Trainees

Abstract: Burnout has a high prevalence among healthcare workers and is increasingly recognised as an environmental problem rather than reflecting a personal inability to cope with work stress. We distributed an electronic survey, which included the Maslach Burnout Inventory Health Services Survey and a previously validated learning environment instrument, to 281 Victorian anaesthetic trainees. The response rate was 50%. We found significantly raised rates of burnout in two of three subscales. Ninety-one respondents (67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(56 citation statements)
references
References 38 publications
2
46
1
7
Order By: Relevance
“…The MBI-HSS comprised 22 questions across 3 subscales; Emotional Exhaustion (EE)-9 questions, Depersonalization (DP)-5 questions, and self-perceived lack of Personal Accomplishment (PA)-8 questions. Responses were scored on a six-point Likert scale (ranging from 0 = never to 6 = everyday) for each subscale, and tabulated into three tiers (low, moderate or high) based on the reference ranges provided with the MBI-HSS: for EE, low (0-16), moderate (17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and high (≥27); for DP, low (0-6), moderate (7)(8)(9)(10)(11)(12) and high (≥13), and finally, for PA, low (≤31), moderate (32)(33)(34)(35)(36)(37)(38) and high (≥39). Burnout was defined by the updated Maslach-recommended criteria of "high EE and high DP" or "high EE and low PA" [22].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MBI-HSS comprised 22 questions across 3 subscales; Emotional Exhaustion (EE)-9 questions, Depersonalization (DP)-5 questions, and self-perceived lack of Personal Accomplishment (PA)-8 questions. Responses were scored on a six-point Likert scale (ranging from 0 = never to 6 = everyday) for each subscale, and tabulated into three tiers (low, moderate or high) based on the reference ranges provided with the MBI-HSS: for EE, low (0-16), moderate (17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and high (≥27); for DP, low (0-6), moderate (7)(8)(9)(10)(11)(12) and high (≥13), and finally, for PA, low (≤31), moderate (32)(33)(34)(35)(36)(37)(38) and high (≥39). Burnout was defined by the updated Maslach-recommended criteria of "high EE and high DP" or "high EE and low PA" [22].…”
Section: Data Collectionmentioning
confidence: 99%
“…Anesthesiology is a stressful specialty and a self-perceived lack of personal accomplishment may be more common because efforts for safe anesthesia are often not acknowledged [6][7][8]. Indeed, recent studies have suggested that burnout is common in anesthesiology residents and trainees [9][10][11]. In a national US study, the prevalence of burnout, distress and depression in 5295 anesthesiology residents were reported as 51%, 32% and 12%, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…A prevalência de nos residentes de anestesiologia Encontrou-se uma alta prevalência de entre os residentes de anestesiologia australianos (n= 140) com 67% deles apresentando evidência desta síndrome em ao menos uma sub-escala EE (49%) e DP (42%), mas baixa de RP (26%), sendo que 10% o tinham nos três aspectos combinados. 6 Este estudo demonstrou um aumento na prevalência em entre os anos de 2008 e 2016, realizado na mesma população, passando de 38,2% (n=108) para 62%, se aproximando da prevalência encontrada em Hong Kong (n=62) em 2008, de 65,1%. 6,7 O maior estudo até o momento foi realizado por de Oliveira 4 , que avaliou através de questionários 54% dos residentes de anestesia americanos (1508 de um total de 2773, responderam a pesquisa).…”
Section: Resultsunclassified
“…Contempla, a exaustão emocional (EE) com 9 questões, a despersonalização (DP) com 5 itens e o baixo grau de realização pessoal (RP) com 8 questões, sendo possível apresentar alteração em qualquer aspecto isoladamente ou uma combinação destes. Uma dificuldade de interpretação dos resultados, está no fato de que o IBM foi extensamente modificado, a versão original foi aplicada na maioria estudos selecionados 6,7 , mas um desses utilizou uma versão sucinta 4…”
Section: Métodosunclassified
“…In this edition of the journal, Castanelli and colleagues investigate the wellbeing of anaesthesia trainees in Victoria 1 . Their findings are deeply concerning-high rates of burnout with "emotional exhaustion" in half and high "depersonalisation" in 42 percent of the 140 trainees who completed the survey.…”
Section: Understanding the Lives Of Anaesthesia Traineesmentioning
confidence: 99%